The Impact of Instagram Influencers on Customer Purchases: Case of the Youth in Harare - Mangoma, Prosper; Chaoyi, Xu; Ondo Mangue, Araceli Ndoho; Adouko Kouah Adjobi, Romuald Paulin (International Journal of Scientific Research and Management (IJSRM), 2022)
Even in the world of purchasing, technological advancements have brought about several changes. The internet has begun to play a major role in assisting customers in finding the things they are seeking for online. With the rise of social media platforms, particularly Instagram, which has become a popular purchasing platform among the youth. Youths are attempting to establish and maintain strong presences on social media platforms, with Instagram being the go-to platform for keeping consumers aware of the latest trends, as more viewers turn to Instagram influencers, their associated trust, and their intention to purchase after being fascinated by them. Influencer marketing is a relatively new notion that is currently gaining traction in the marketing process, and it is linked to human purchasing intents. The current study aims to investigate the numerous marketing strategies used by youth Instagram influencers, as well as their impact on customer purchase. The study also examines the impact of using various users such as celebrities, bloggers, and others, as well as their reach. The current study examines the responses of 200 youths in Harare, Zimbabwe and their primary influencers on purchase decisions